Groundwater modeling for the resource development - Zawawi, Mohamed Azwan; Said, Salim (Universiti Putra Malaysia, 1999)
The amount of groundwater in nature has been estimated to be 97% of the total freshwater available. Based on this fact, knowledge about groundwater is needed to use this resource for different purposes especially during the dry season when serious shortage of surface water occurs. In this study, a mathematical model called Groundwater Modeling System (GMS) was used for groundwater monitoring and visualization in some selected areas. Pumping test was carried out to collect the necessary data for running the GMS model. Besides the GMS model, GIS software was used to prepare the necessary mapping to run the GMS model. The basic application of the GMS model revealed that this model was effective in making a decision whether the groundwater of the tested area is suitable for water supply development or not.